Prevalence and associated factors of faecal incontinence among community- dwelling older adults in Pahang, Malaysia - Harun, Nor Jannah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2024)
PURPOSE: This study aims to investigate the prevalence of FI and identify associated factors among community-dwelling older people in Pahang. METHODS: This study is a cross-sectional survey. Respondents were recruited from Senior Citizen’s Activity Centres using simple random sampling. A set of questionnaires was completed using a guided self-completion method. Multiple logistic regression analysis was used to identify associated factors. RESULTS: A total of 72 respondents were recruited with a mean age of 67.14 years (SD = 4.21). About 87.5% were Malay, and 59.7% were women. The prevalence of FI was 47.2%. Among those with FI, 67.6% reported a small amount of faecal leakage that stained their underwear, 26.5% had a moderate amount, and 5.9% reported a large amount of recurrent stool leakage. About 38.2% experienced leakage 2 to 3 days a month, and 35.3% experienced leakage 1 to 3 days a week. Loose or watery stool (OR = 4.21, 95% CI = 1.38, 12.81; P = 0.011) and lumpy or hard stool (OR = 6.00, 95% CI = 1.44, 25.0; P = 0.014) were significantly associated with FI. CONCLUSION: This study reveals a high prevalence of FI among community-dwelling older people in Pahang, with both loose or watery stool and lumpy or hard stool significantly associated with FI. Targeted interventions and healthcare strategies are needed to manage and mitigate the burden of FI in this population.